A practical marker to determining acute severe ulcerative colitis: CRP/albumin ratio - Sayar, Suleyman (North Clin Istanb, 2019)
OBJECTIVE: There are many instruments to measure disease activity in ulcerative colitis. While determining clinical activity according to these instruments, many clinical and laboratory parameters are needed to be followed. Determination of disease activity with non-invasive and objective inflammatory indicators may be a practical and objective way. CRP/Albumin ratio (CAR) is an inflammatory marker that is considered to have prognostic value in various cancers, sepsis and acute pancreatitis. In this study, we aim to investigate diagnostic performance CAR in determining the clinical severity of ulcerative colitis. METHODS: Between November 2011 and February 2017, hospital records and follow-up cards of patients with ulcerative colitis were reviewed retrospectively. One hundred forty-nine patients were included in this study. Patient’s demographic data, laboratory values, clinical disease activity, according to Truelove & Witts criteria and endoscopic activity according to the Mayo sub-score and treatments, were recorded. Diagnostic performance of CAR analyzed to determine the clinical severity. RESULTS: Of the patients included in this study, 99 (62%) were male, and 50 (38%) were female. Mean age was 45.22±14 years. When patients were grouped into remission, mild, moderate and severe disease according to disease activity, there was a statistically significant difference between CRP, CAR, erythrocyte sedimentation rate (ESR) and albumin levels (p=0.001; p<0.05). Area under the curve (AUC) values for the diagnosis of severe disease were 0.941, 0.931, 0.888 and 0.883 for CAR, CRP, ESR and albumin levels, respectively. Cut-off value to determine severe disease for CAR was 0.6 (sensitivity: 88.9%, specificity of 90.3%, positive predictive value (PPV) 85.1%, negative predictive value (NPV) 92.8%, AUC: 0.941, p<0.001). CONCLUSION: There was a significant relationship between CAR, CRP, ESR and albumin levels and clinical disease severity in patients with ulcerative colitis. CAR is a cheap and practical marker for the diagnosis of acute severe ulcerative colitis.